Perception of authors in e-publishing - Shiratuddin, Norshuhada; Othman, Zakirah; Ahmad, Khairul Bariah; Hassan, Shahizan (Internet Scientific Publications LLC, 2006)
Electronic and printed publications have their own strength values. Both formats are required for greater information dispersal. In this digital economy era, Internet becomes popular as a medium to market and share information. Hence, this paper describes the model. for publishing and marketing Universiti Utara Malaysia (UUM) electronic publication (e Publication). A publishing model, which consists of eleven stages, was followed to ensure quality publication. This project was confined to educational environment and a virtual centre called Electronic Information Centre (eInfoC) was developed to collaborate with an independent electronic publisher (eloka.com). The objective of this paper is to report authors perception on models developed and several satisfaction issues. Findings indicated that the e-Publishing model that was suggested in this project was well accepted by 80% of the authors and e Books do have a positive future in higher educational environment.